Electronic prescribing in paediatric secondary care: are harmful errors prevented?. Issue 9 (7th June 2019) - Fox, Andy; Portlock, Jane; Brown, David
Abstract : Objective: The aim of this research was to ascertain the effectiveness of current electronic prescribing (EP) systems to prevent a standardised set of paediatric prescribing errors likely to cause harm if they reach the patient. Design: Semistructured survey. Setting: UK hospitals using EP in the paediatric setting. Outcome measures: Number and type of erroneous orders able to be prescribed, and the level of clinical decision support (CDS) provided during the prescribing process. Results: 90.7% of the erroneous orders were able to be prescribed across the seven different EP systems tested. Levels of CDS varied between systems and between sites using the same system. Conclusions: EP systems vary in their ability to prevent harmful prescribing errors in the hospital paediatric setting. Differences also occur between sites using the same system, highlighting the importance of how a system is set up and optimised.